2008
DOI: 10.1063/1.3021065
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulation of deformation/motion of a drop suspended in viscous liquids under influence of steady electric fields

Abstract: The deformation / motion of a droplet suspended in a viscous liquid under the influence of an applied external electrical field are investigated through numerical simulations. The two-phase flow field of the drop suspension system is simulated using a front tracking / finite volume method for solving the full Navier-Stokes equations. Three different electric field models are applied in order to take into account the effects of the electric field, electric charge, and electrical properties of liquids. Drops wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
74
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 141 publications
(80 citation statements)
references
References 26 publications
4
74
0
2
Order By: Relevance
“…However, this method is not used to model coalescence or pinch-off, since one weakness of VOF is that it can not distinguish topological changes precisely. The current literature also includes a fronttracking finite volume method that can model electric charge on the droplet surface [18]. In addition, mesoscopic methods such as Lattice Boltzmann methods have been used for simulating drop deformation using electric fields [41,14].…”
Section: Overview Of Numerical Approachesmentioning
confidence: 99%
“…However, this method is not used to model coalescence or pinch-off, since one weakness of VOF is that it can not distinguish topological changes precisely. The current literature also includes a fronttracking finite volume method that can model electric charge on the droplet surface [18]. In addition, mesoscopic methods such as Lattice Boltzmann methods have been used for simulating drop deformation using electric fields [41,14].…”
Section: Overview Of Numerical Approachesmentioning
confidence: 99%
“…The results indicated that the interpolation scheme to smoothen the electric properties (conductivity and permittivity) in the interface transition region had a significant influence on the solution in the bulk [17]. Hua et al summarized three different kinds of electric fields: leaky dielectric model, perfect dielectric model, and constant charge model and numerically investigated the deformation of droplet and internal flow inside droplet by employing the interface tracking method where the interface was considered to have a finite thickness of the same order as the mesh size instead of zero thickness [18]. Lin et al proposed the phase field method to study the two-phase electrohydrodynamic flow which was generated by electric field.…”
Section: Introductionmentioning
confidence: 99%
“…But this method is inaccurate for the calculation of surface tension. Some methods which treated the interface as a finite width region where the physical properties continuously transitioned from one phase to another phase were presented in recent years [16][17][18][19]. Zhang and Kwok investigated the droplet deformation driven by electrohydrodynamics using a multicomponent LBM method that a cosine function was employed to describe such transition interface.…”
Section: Introductionmentioning
confidence: 99%
“…Explicit approaches, such as boundary integral and front-tracking methods, track discrete points on the interface surface. The motion and deformation of droplets under the presence of an electric field [8][9][10][11][12] [14][15][16][17][18][19][20]. Each implicit technique to represent the interface has its own advantages and drawbacks.…”
Section: Introductionmentioning
confidence: 99%